Teknik Wawancara Internasional: Persiapan, Komunikasi, Etika, dan Strategi Menjawab Pertanyaan dalam Seleksi Pekerjaan Global - Tri Wahyuni; Edomi Saputra (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
Globalization, advances in digital technology, and increasing workforce mobility have transformed the way multinational companies conduct recruitment, making international interviews a critical stage in assessing candidates’ competence, personality, and cultural fit. This study aims to describe preparation strategies, effective communication, professional ethics, and structured approaches to answering questions required by candidates facing international interviews. This research employs a qualitative method through a library research approach, collecting, reviewing, and analyzing academic sources such as journal articles, books, and relevant prior studies on international interviews. The findings indicate that candidates’ success in international interviews is determined by four main aspects: (1) thorough preparation, including understanding the company profile, preparing professional documents, mastering foreign languages, conducting mock interviews, and ensuring technical readiness for online interviews; (2) effective communication, encompassing structured verbal communication, rapport building, optimized nonverbal communication, active listening, and adaptation to technology; (3) professional ethics and attitude, such as neat appearance, courtesy, integrity, cross-cultural sensitivity, and post-interview etiquette; and (4) the application of structured strategies such as the present–past–future approach and the STAR (Situation, Task, Action, Result) method in answering experience-based questions. This study concludes that the integrated mastery of these four aspects can enhance candidates’ chances of success in the global job selection process.